2016
DOI: 10.1089/jwh.2016.5761
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index as a Measure of Obesity: Racial Differences in Predictive Value for Health Parameters During Pregnancy

Abstract: Background: As a measure of obesity, body mass index (BMI; kg/m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The observed interaction between BMI, race, and leptin level indicates that in the obese state leptin levels may be differentially regulated between black and white women. Of note, prior data from others, as well as our group, indicates that the predictive value of BMI varies based on race ( Gillespie and Christian, 2016 ). For example, prior data from our group show that BMI is more strongly associated with both serum cytokine levels and birthweight among pregnant European American than black women ( Gillespie and Christian, 2016 ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The observed interaction between BMI, race, and leptin level indicates that in the obese state leptin levels may be differentially regulated between black and white women. Of note, prior data from others, as well as our group, indicates that the predictive value of BMI varies based on race ( Gillespie and Christian, 2016 ). For example, prior data from our group show that BMI is more strongly associated with both serum cytokine levels and birthweight among pregnant European American than black women ( Gillespie and Christian, 2016 ).…”
Section: Discussionmentioning
confidence: 60%
“…Of note, prior data from others, as well as our group, indicates that the predictive value of BMI varies based on race ( Gillespie and Christian, 2016 ). For example, prior data from our group show that BMI is more strongly associated with both serum cytokine levels and birthweight among pregnant European American than black women ( Gillespie and Christian, 2016 ). It has been suggested that this may be due to differential fat distribution in women of different races.…”
Section: Discussionmentioning
confidence: 60%
“…There are significant differences on body structure, BMI classifications, race and ethnicity between these populations and Chinese population 1416,28 . In fact, several studies showed that pre-pregnancy BMI was associated with birth weight among European Americans but not African Americans, suggesting a racial/ethnic difference on the relationship between pre-pregnancy BMI and fetal growth 29,30 ; secondly, negative results came most frequently from small samples 17 ; Lastly, animal studies demonstrated that pre-pregnancy and/or gestational high fat diets (HFD)-induced obesity differentially disturbed fetal growth development 18,19,31 . Pre-pregnancy HFD-induced obesity caused fetal SGA.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index may not be an accurate measurement of determining body fat difference between African Americans and European Americans, as it is well documented that African Americans generally have higher lean mass and lower fat mass. [40][41][42] African Americans may have a higher body mass index because they generally have more muscle mass as opposed to fat mass, which is linked with poor cardiovascular and cerebrovascular health. [43][44][45] Future studies should investigate the insidious effects of obesity on white matter integrity over time.…”
Section: Limitationsmentioning
confidence: 99%